Identifikasi Tumbuhan Penyusun Vegetasi Pulau Kumala sebagai Kawasan Delta Sungai Mahakam Kalimantan Timur - Hidayah, Maulida Ulfa; Agil, Muhamad; Mahmud, Muchammad Eka (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Indonesia has islands that are very numerous and even reach tens of thousands. Each island is overgrown with different types of plants with their own characteristics including Kumala Island in East Kalimantan. Kumala Island is a delta of the Mahakam River that formed by river flow. The island is overgrown with many plants of various types. The diversity of plant species found on this island has never been identified so it becomes very interesting and important to conduct research related to plant identification as a conservation effort. This study aims to identify all types of plants found on Kumala Island as a form of conservation of the plants, on Kumala Island. The method used in this study is exploration of the predetermined research area. Each plant found was subjected to morphological observations, and the type was identified. The plant data obtained were analyzed using qualitative descriptive techniques. The results showed that 88 types of plants were identified consisting of 28 types of trees, 48 types of shrubs and 12 types of grass. The number of families identified was 44 families, of which 18 families included tree species, 24 families included shrub species and 2 families included grass species. The existence of plants on Kumala Island needs to be considered and conserved so that their existence remains protected.